Triazole linker-based trivalent sialic acid inhibitors of adenovirus type 37 infection of human corneal epithelial cells1. Issue 35 (21st September 2015) - Caraballo, Rémi; Saleeb, Michael; Bauer, Johannes; Liaci, A. Manuel; Chandra, Naresh; Storm, Rickard J.; Frängsmyr, Lars; Qian, Weixing; Stehle, Thilo; Arnberg, Niklas; Elofsson, Mikael
<x xml:space="preserve">Abstract</x> Adenovirus type 37 (Ad37) is one of the principal agents responsible for epidemic keratoconjunctivitis (EKC), a severe ocular infection that remains without treatment.